2023
DOI: 10.2147/prbm.s408792
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Experienced Long Working Hours and Depression, Anxiety, and Suicidal Ideation Among Chinese Medical Residents During the COVID-19 Pandemic: A Multi-Center Cross-Sectional Study

Abstract: Background Long working hours are common among medical residents and may increase the risk of mental disorders. We aimed to investigate the association between experienced long working hours and depression, anxiety, and suicidal ideation among Chinese medical residents during the COVID-19 pandemic. Methods This study was conducted in September 2022; 1343 residents from three center in Northeastern China were included in the final analysis (effective response rate: 87.61… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
2
1
Order By: Relevance
“…In a previous study, it was found that working over 80 h per week increased the risk of depression among residents ( Awan et al, 2022 ). However, in contrast with previous findings ( Ogawa et al, 2018 ; Li et al, 2023 ), the BASIL study did not find a significant association between working hours and mental health status. This difference could be attributed to the fact that our study pertained to wellbeing and psychological distress rather than to depression.…”
Section: Discussioncontrasting
confidence: 99%
“…In a previous study, it was found that working over 80 h per week increased the risk of depression among residents ( Awan et al, 2022 ). However, in contrast with previous findings ( Ogawa et al, 2018 ; Li et al, 2023 ), the BASIL study did not find a significant association between working hours and mental health status. This difference could be attributed to the fact that our study pertained to wellbeing and psychological distress rather than to depression.…”
Section: Discussioncontrasting
confidence: 99%
“…Meanwhile, compared to the research conducted at the COVID-19 outbreak’s onset, our study’s results are also significantly higher than those of prison officers in China (33.43%) and in the United States (38, 32%), as mentioned above ( 24 , 25 ). Moreover, the mental health status of prison officers in this study was worse than that of other groups in China—including older adults, perinatal women, and medical residents ( 40 , 41 , 54 )—who were also evaluated during the prolonged COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 91%
“…In this study, Cronbach’s α for the PHQ-9 was 0.947. A total score of ≥5 was adopted to identify individuals with the presence of mild to severe anxiety or depressive symptoms ( 40 , 41 ).…”
Section: Methodsmentioning
confidence: 99%